A manager's guide to financial analysis : powerful tools for analyzing the numbers and making the best decisions for your business - Sherman, Eliot H. (AMA, American Management Association, 2015)
This course gives students the tools they need to crunch the numbers, focusing on prediction rather than reporting. Students will learn how to: connect a company's past experience to future expectations; apply correct analytical techniques to problems or decisions; identify and explain deviations from anticipated results; make needed adjustments to financial statements, taking into account current values, off-balance-sheet financing, and unrecognized items; use financial ratios to analyze trends, identify issues, and compare results to the competition and industry; evaluate capital investments using net present value, internal rate of return, profitability index, and other methods; manage current assets including cash, credit and collections, and inventory; build a robust financial forecast; determine a company's optimal capital structure and debt policy; measure the financial impact of a merger or acquisition. --